Pengaruh Kualitas Pelayanan dan Grooming Pemandu Wisata di Objek Istano Basa Pagaruyuang - Mandalia, Siska; Zonata, Yuke; Wulandari, Wiranda (LPPM STP ARS Internasional, 2024)
ABSTRACT The main problem in this study is whether the service quality and grooming of tour guides influence tourist satisfaction at the Istano Basa Pagaruyuang Tourism Object. This study aimed to determine the effect of service quality and grooming of tour guides at the Istano Basa Pagaruyuang tourist attraction. The method used in this research is a quantitative research method. The data collection technique was carried out by filling out a questionnaire. The number of respondents is 100 people. The data analysis technique used is a validation test, reliability test, normality test, multiple linear regression analysis, partial t-test, simultaneous f test, and test of the coefficient of determination. The study results show that the service quality variable partially influences tourist satisfaction. However, the tour guide Grooming variable does not control tourist satisfaction variables. From the results of the f test, it is obtained that the variables of service quality and grooming simultaneously affect tourist satisfaction.